2016
DOI: 10.1056/nejmoa1515990
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen versus Ibuprofen in Young Children with Mild Persistent Asthma

Abstract: BACKGROUND Studies have suggested an association between frequent acetaminophen use and asthma-related complications among children, leading some physicians to recommend that acetaminophen be avoided in children with asthma; however, appropriately designed trials evaluating this association in children are lacking. METHODS In a multicenter, prospective, randomized, double-blind, parallel-group trial, we enrolled 300 children (age range, 12 to 59 months) with mild persistent asthma and assigned them to receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 18 publications
(21 reference statements)
0
66
0
5
Order By: Relevance
“…Details of that study were previously published. 20 Children were randomized in two processes: the first determined the crossover sequence of asthma therapy and the second determined the blinded antipyretic/analgesic medication to be used as needed for fever or pain throughout the 48 week duration of the crossover study, with stratification by clinical center.…”
Section: Methodsmentioning
confidence: 99%
“…Details of that study were previously published. 20 Children were randomized in two processes: the first determined the crossover sequence of asthma therapy and the second determined the blinded antipyretic/analgesic medication to be used as needed for fever or pain throughout the 48 week duration of the crossover study, with stratification by clinical center.…”
Section: Methodsmentioning
confidence: 99%
“…Acetaminophen (APAP), an analgesic and antipyretic agent, is better known as paracetamol in many countries. APAP is used in adults and children worldwide with a safety profile in therapeutic doses [4][5][6]. However, excessive APAP can cause severe hepatotoxicity, nephrotoxicity, and even death in experimental animals and humans [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested an association between acetaminophen and the development or exacerbation of asthma 44 and alteration of immune response in children. 45,46 Findings are, however, conflicting and several confounding factors (treatment indication and concomitant viral respiratory infection) might contribute to this positive correlation.…”
Section: Acetaminophenmentioning
confidence: 99%